Back Cover: Quadruplex DNA‐Stabilising Dinuclear Platinum(II) Terpyridine Complexes with Flexible Linkers (Chem. Eur. J. 7/2016). Issue 7 (2nd February 2016) - Ang, Dale L.; Harper, Benjamin W. J.; Cubo, Leticia; Mendoza, Oscar; Vilar, Ramon; Aldrich‐Wright, Janice
Abstract : G‐quadruplex DNA (QDNA) has been shown to play a role in gene expression, with implications in cell mortality and oncogenesis. Compounds that are capable of preferentially binding to and stabilising QDNA structures are seen as potential novel cancer treatments. The dinuclear platinum complex, pictured, exhibits strong preference for QDNA over dsDNA, resulting in increased stability of the QDNA motif. A synchrotron radiation circular dichroism melt spectrum is included to convey the increased spectral complexity these motifs possess. More information can be found in the Full Paper by R. Vilar, J.  Aldrich‐Wright, et al. onpage 2317 ff.